Prototipo y simulación cad de una camilla tipo cuchara a base de guadua angustifolia kunth (2018)
Many times the accidents, the risks and the contingencies is inevitable, but manageable if a prehospitable attention is contributed (APH) eficient, but unfortunately is a significant digit of poverty in Colombia, which affects to the APH to not having sufficient resources, like the stretchers, so to this article the implementation of Guadua paid attention like objective angustifolia Kunth like structural material for a stretcher type spoon, widely used in the APH in emergency and contingencies in which the patients present injuries concerning the spinal marrow, which they can jeopardize his central nervous system.For this, angustifolia Kunth was important to have a more complete understanding for the Guadua, in relation to the knowledge of its mechanical resistance that is accepted by the application of destructive tests of resistance contemplated by Norma Technical Columbiana: NTC 5525 and non-destructive testing, like the infrared thermography. With this, a more precise point of view of mechanical resistance was obtained, and thus to be able to generate the model of the concept of a structural base of a stretcher type spoon in Guadua Angustifolia Kunth, computer-assisted (CAD) and, next, simulated by means of finite elements in terms of linear efforts.